TERORISME DALAM PERSPEKTIF PSIKOLOGI AGAMA - intan05 dwi sari; Taufik Kurnia Rohim; Fardan Nuari Sukarno; Takiuddin -; Riski Hidayati (Al Ghazali, 2021)
Abstract Terrorism is a serious threat to state sovereignty, because it poses a danger to security, peace, and harms the welfare of the people. The cause of terrorism is due to economic motives, revenge and based on certain beliefs in each individual. Terrorism, which is an extraordinary crime, needs to be dealt with by using extraordinary means. To prevent and combat terrorism, since before the prevalence of incidents classified as forms of terrorism occurred in the world, the international and regional communities as well as various countries have tried to carry out criminal policies accompanied by systematic and comprehensive criminalization of acts categorized as terrorism. Keywords: terrorism, psychology, religion Abstract Terrorism is a serious threat to state sovereignty, because it poses a danger to security, peace, and harms the welfare of the people. The cause of terrorism is due to economic motives, revenge and based on certain beliefs in each individual. Terrorism, which is an extraordinary crime, needs to be dealt with by using extraordinary means. To prevent and combat terrorism, since before the prevalence of incidents classified as forms of terrorism occurred in the world, the international and regional communities as well as various countries have tried to carry out criminal policies accompanied by systematic and comprehensive criminalization of acts categorized as terrorism. Keywords: terrorism, psychology, religion Abstrak Abstract Terrorism is a serious threat to state sovereignty, because it poses a danger to security, peace, and harms the welfare of the people. The cause of terrorism is due to economic motives, revenge and based on certain beliefs in each individual. Terrorism, which is an extraordinary crime, needs to be dealt with by using extraordinary means. To prevent and combat terrorism, since before the prevalence of incidents classified as forms of terrorism occurred in the world, the international and regional communities as well as various countries have tried to carry out criminal policies accompanied by systematic and comprehensive criminalization of acts categorized as terrorism. Keywords: terrorism, psychology, religion Abstrak Terorisme merupakan salah satu ancaman serius terhadap kedaulatan negara, karena menimbulkan bahaya terhadap keamanan, perdamaian, serta merugikan kesejahteraan masyarakat. Penyebab terjadinya terorisme yaitu karena motif ekonomi, balas dendan dan berdasar pada aliran kepercayaan tertentu pada setiap individu. Terorisme yang merupakan kejahatan luar biasa membutuhkan penenganan dengan mendayagunakan cara-cara luar biasa. untuk mencegah dan memerangi terorisme tersebut, sejak sebelum maraknya kejadian yang digolongkan sebagai bentuk terorisme terjadi didunia, masyarakat internasional maupun regional serta berbagai negara telah berusaha melakukan kebijakan kriminal disertai kriminalisasi sistematik dan komprehensif terhadap perbuatan yang dikategorikan sebagai terorisme.